Subclavian steal syndrome – surgical or endovascular treatment - Cvetić, Vladimir Z; Čolić, Momčilo; Radmili, Oliver; Banzić, Igor; Končar, igor; Lukić, Borivoje; Davidović, Lazar (Vojnosanitetski pregled, 2018)
Background/Aim. A phenomenon of subclavian steal is caused by occlusion or stenosis of the proximal subclavian artery with subsequent retrograde filling of the subclavian artery via the ipsilateral vertebral artery. The aim of this research was to compare surgical method [carotid-subclavian bypass grafts (CSBG)] and endovascular methods [percutaneous transluminal angioplasty (PTA) and stenting of subclavian artery] from the aspect of immediate and long-term results. Methods. Thirty patients [16 (53.33%) males], of average age between 60.1 ± 8.25 years were treated with CSBG and compared with a group of forty patients [18 (45%) males], of the average age between 57.75 ± 6.15 years treated by PTA and stenting of subclavian artery. Immediate and long-term results were determined clinically and confirmed by Doppler pressures and duplex ultrasound/angiography. All patients were followed-up after 1, 6 and 12 months post-procedure, and annually thereafter. Results. The average follow-up for both groups was 22.37 ± 11.95 months. There were 2 (6.67%) procedural complications in the CSBG group (transient ischemic attack in 2 patients) and 3 (7.5%) ones in the PTA/stent group (dissection and distal embolization in one patient and puncture site hematoma in one patient). Systolic blood pressure difference between the two brachial arteries in CSBG group was: 42.6 ± 14.5 mmHg vs 4.75 ± 12.94 mmHg (p < 0.05). In the PTA/stent group it was: 41.2 ± 15.35 mmHg vs 3.58 ± 5.83 mmHg (p < 0.05). Long-term success was 93.33% in the CSBG group and 92.5% in the PTA/stent group (p > 0.05). Conclusions. Both, the CSBG and PTA/stenting of subclavian artery are safe, efficacious and durable procedures. They have similar immediate and long-term results. PTA and stenting are the methods of choice for high grade stenosis, near total occlusions and segment occlusions of subclavian artery. CSBG is indicated in case of diffuse occlusive lesions and when the PTA and stenting do not succeed or cause complications.